Effect Size Model Pembelajaran Visualization Auditory Kinestetic (VAK) Terhadap Hasil Belajar IPA di Sekolah Dasar - Asri Mulyani; Anak Agung Gede Agung; I Nyoman Laba Jayanta (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
There is no recent research that examines the results of research on the Visualization Auditory Kinesthetic learning model on science learning outcomes at the elementary school level. This study aims to analyze the influence of the Visual Auditory Kinesthetic (VAK) learning model on science learning outcomes in elementary schools. The method used is a meta-analysis of a narrative review or systematic review by analyzing the results of research that have been published nationally related to the use of the Visual Auditory Kinesthetic model of learning outcomes in science in elementary schools. The sample of analysis is five journals that have been published in the period 2013-2020, which discuss the writing of experiments using the Visual Auditory Kinesthetic model of science learning outcomes. The approach used is descriptive quantitative, namely calculating the effect size by identifying the mean, standard deviation, and variance of the t-test calculation. The writing instrument is a coding sheet that summarizes the data and journal information. Based on the results of the overall effect analysis, the average value of the influence is 3.67, which means that it is in the large effect category. The analysis findings also show that the Visual Auditory Kinesthetic learning model provides an effective influence in terms of the area and the dependent variable as well as the learning media used. In each article that has been analyzed for the effect size, there are differences in the results of the Visual Auditory Kinesthetic learning model which is assisted by learning media, and those that are not assisted by learning media. learn science in elementary school.